Pendidikan Islam Berbasis Digitalisasi - Rizka Zulmi; Ardila Putri Noza; Reza Anke Wandira; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This article is intended to discuss formulations Islamic education in the digital era and the outcomes to be achieved from the Islamic education. With the emergence of the digital era, students ingenerally as a digital native, since birth immediately know technology so that it is very easy for them to use it different from adults who mostly occupy positions as digital migrants. The format of Islamic Education must be designed in accordance with the lifestyle of students in the millennial era. This writing is a synthesis of thought with a qualitative approach to explore previous thoughts and findings for formulate new thinking in response to challenges and opportunities in the technological age. Two things need to be developed in islamic education, namely the digitization of the material taught and encouraged generation of Muslims achieve the hasanah life in this world and the hereafter.